Northwest History. Alaska. Dogs, Dog Races & Mushers. (1936)
Girl Musher Feared Lost; Long Overdue. GIRL WUSHER FEARED LOST; LOW OVERDUE FAIRBANKS, Alaska, Feb. 28. (/P)—Fears that diminutive Mary Joyce, 27-year-old dog musher, may have met disaster somewhere along her wilderness trail, were felt here today as she was reported five days overdue at Tanana Crossing, a telegraphic communication station 150 miles southeast of here. She has not been reported since she mushed out of Burwash Landing, Yukon Territory. The comely Taku Lodge mistress, from southeastern Alaska, left Burwash with her five dogs and a lone Indian guide named Jimmy Allen. The temperature at that time was 48 degrees below zero. The 300-mile route from Burwash, on the northwestern side of Kluane lake, to Tanana Crossing is over a sparsely settled, frozen wilderness. There are no roads, no villages, and only a few native huts. Several ice-caked rivers and streams cross the area. Miss Joyce left Taku December 22 for Fairbanks, 1,000 miles due north. She is traveling over the, long inland route, over the mountains, and down the Yukon watershed region. She said she was making the dog-sled journey "just for the experience." She is keeping a diary of her experiences. Officials of the Fairbanks Ice Carnival and Dog Derby were also anxious. Miss Joyce is Juneau's eniry in the beauty contest to select Miss Alaska, ruler of the carnival, next week.